The identity features of the intervention model of educational inspection in Andalusia - Luna Ariza, Pedro Ángel (Avances en Supervisión Educativa, 2014)
It is hard to imagine Inspectorate of Education in Andalusia without an intervention model approved and stable oriented to improve students achievement. Dedication to the IFC (Key Factors Intervention) and its supervision in schools and classrooms of Andalusia is a differentiating factor . It is an intervention model that goes beyond the simple verification of standars compliance, where the visit and report are the main tools of the inspector. The main features of its identity are the number of methodological elements, as contrasted data analysis, which provides a systemic view of the school organization and other functional aspects , such as open level, open reference and teamwork.
Keywords: educational inspection; intervention on key factors; improving educational achievement; approval; open level; open reference; teamwork